Applying Al-Ta’lil bi Al-Hikmah to Social Media Use: A Complementary to the Maqasid Shariah Approach in Islamic Digital Ethics - Lokman, Md Azzaat Ahsanie; Mohd Noor, Muaz; Mohamad Nadzli, Nurin Sofiya; Suyurno, S Salahudin; Harun, Muhammad Safwan; Kayadibi, Saim (Millah: Journal of Religious Studies, 2026)
The rapid expansion of social media has generated significant ethical challenges, including misinformation, harmful online discourse, privacy erosion, and excessive digital consumption. Although Islamic ethics has increasingly engaged these issues, primarily through Maqasid Shariah-based frameworks, existing approaches often remain too general to guide the everyday moral decisions faced by individual users in digitally mediated environments. Addressing this gap, this study examines the application of al-Ta’lil bi al-Hikmah, a jurisprudential method that derives ethical judgment from the underlying wisdom (hikmah) of Islamic norms, to contemporary social media use. Employing a qualitative jurisprudential analysis grounded in usul fiqh, the study conducts an interpretive textual analysis of Quranic injunctions, Prophetic traditions, and classical juristic discussions to identify core ethical wisdom related to communication, privacy, moderation, and accountability. These insights are then thematically applied to key domains of social media practice, including content sharing, online criticism, time management, and the ethical implications of algorithmic influence at the level of user behaviour. The analysis demonstrates that a hikmah-centred approach enables more nuanced moral discernment than rule-based or exclusively Maqasid-oriented models by translating higher ethical objectives into actionable guidance for individual digital conduct. Conceptually and methodologically, this study advances Islamic digital ethics by operationalising al-Ta’lil bi al-Hikmah as a complementary framework that refines Maqasid reasoning at the micro-ethical level. In doing so, it offers a principled yet flexible model for ethical social media engagement that aligns individual integrity with broader Islamic moral objectives.